2020
DOI: 10.3390/insects11090562
|View full text |Cite
|
Sign up to set email alerts
|

Deep Sequencing of Small RNAs in the Whitefly Bemisia tabaci Reveals Novel MicroRNAs Potentially Associated with Begomovirus Acquisition and Transmission

Abstract: The whitefly Bemisia tabaci (Gennadius) is a notorious insect vector that transmits hundreds of plant viruses, affecting food and fiber crops worldwide, and results in the equivalent of billions of U.S. dollars in crop loss annually. To gain a better understanding of the mechanism in virus transmission, we conducted deep sequencing of small RNAs on the whitefly B. tabaci MEAM1 (Middle East-Asia Minor 1) that fed on tomato plants infected with tomato yellow leaf curl virus (TYLCV). Overall, 160 miRNAs were iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Then, with the use of RNA as a template, the steps of reverse transcription were carried out following the specification of the Mir-X miRNA First-Strand Synthesis Kit (TaKaRa, China). A total of 10 miRNAs (miR-1-3p, miR-9a, miR-11, miR-184, miR-100-5p, miR-275, miR-252a, miR-279d, miR-277, and miR-624) and U6 snRNA, one commonly used reference gene, were set as the candidates for evaluation, according to the published database of B. tabaci miRNA-seq and our database (Wang et al, 2016;Li et al, 2018;Hasegawa et al, 2020). Primers of the candidate miRNA were designed in utilizing the software of Primer 5.0 based on the specification of the Mir-X miRNA First-Strand Synthesis Kit (TaKaRa, China), and the reverse primer of all miRNAs was a universal reverse primer (mRQ 3′Primer) from the kit.…”
Section: Extraction Of Rna Synthesis Of Cdna and Design Of Primersmentioning
confidence: 99%
See 1 more Smart Citation
“…Then, with the use of RNA as a template, the steps of reverse transcription were carried out following the specification of the Mir-X miRNA First-Strand Synthesis Kit (TaKaRa, China). A total of 10 miRNAs (miR-1-3p, miR-9a, miR-11, miR-184, miR-100-5p, miR-275, miR-252a, miR-279d, miR-277, and miR-624) and U6 snRNA, one commonly used reference gene, were set as the candidates for evaluation, according to the published database of B. tabaci miRNA-seq and our database (Wang et al, 2016;Li et al, 2018;Hasegawa et al, 2020). Primers of the candidate miRNA were designed in utilizing the software of Primer 5.0 based on the specification of the Mir-X miRNA First-Strand Synthesis Kit (TaKaRa, China), and the reverse primer of all miRNAs was a universal reverse primer (mRQ 3′Primer) from the kit.…”
Section: Extraction Of Rna Synthesis Of Cdna and Design Of Primersmentioning
confidence: 99%
“…Previously, the screening of suitable reference genes for mRNA in B. tabaci had been conducted (Li et al, 2013), and the results were contributed to the studies on mechanisms of insecticide resistance, plant virus-host interactions, chemical sensing, and host preference in whitefly (Wei et al, 2017;Xu et al, 2019;Zeng et al, 2019;He et al, 2020;Wang et al, 2020a,b;Yang et al, 2020). In recent years, several microRNA profiles of B. tabaci under different treatments have been published (Wang et al, 2016;Li et al, 2018;Hasegawa et al, 2020), but as an essential precondition, suitable reference genes of B. tabaci for analyzing the expression of miRNA have not been selected and evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Introduction of microRNA‐184 that targeting the dengue virus type 4 genome results in a significant restriction of virus replication in mosquitoes 14 . The miR‐184‐3p has been identified as an abundant conserved miRNA in insects that transmit plant viruses, such as Laodelphax striatellus (Fallén), S ogatella furcifera (Horváth), and Bemisia tabaci 15–18 . Although the function of microRNA‐184 in regulating animal viruses has been studied, its function in the plant virus–insect interaction has not been well investigated.…”
Section: Introductionmentioning
confidence: 99%
“…An understanding of the regulatory gene networks of whiteflies can help identify targets for RNA interference control of whiteflies. Therefore, Hassagawa et al conducted research which revealed a comprehensive microRNA regulatory system in the whitefly B. tabaci and this may be involved in virus acquisition and transmission [ 10 ].…”
Section: Introductionmentioning
confidence: 99%